Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages COMMON WEALTH PUBLICATIONS (Distributed by the Socialist Book Centre, Ltd., 161a, The Strand, London.) GENERAL. Common Wealth Policy, 1944-45 3/6 Branch Handbook for Members Only 3/- Facts for Socialists 1/6 Report of the Annual Conference, 1944 1/- Election Handbook for Members Only 1/- Manifesto 6d. Trade Unions and Common Ownership 6d. Constitution 6d. Full Employment 6d. Questions and Answers 6d. INFORMATION BULLETINS. No. No. 1. Education (revised)............ 6d. 5. The Policies of the Left 6d. 2. Representative Government 6d. *6. Poverty and Inequality 6d. 3. Housing and Planning 6d. *7. Monopoly 6d. 4. The Health Services 6d. *8. The National Income 6d. *No. 9 Election Facts............ 6d. POPULAR LIBRARY. In preparation. No. No. 1. Here are your Answers J. B. Priestley ......... 6d. *6. Child Delinquency James Hemming 2. The German Problem H.N. Brailsford ..... 6d. *7. The Seven Pillars of Peace Olaf Stapleton 3. Religion and the New Society K. Ingram............... 6d. *8. Letters to a Soldier J.B. Priestley 4. Beveridge Report B. Wootton.......6d. *9. Personal and Social Values John Macmurray 5. Democratic Education St. John Reade & D. Sargant 6d. *10. Rights of Individuals Harry Roff LEAFLETS. 1943. Notes on Common Ownership 2d. No Unemployment under Common Ownership 2d. Sir Richard Ackland States Our Case in Parliament 2d. India 2d. Common Wealth and the Beveridge Report 2d. Women in the New Age 2d. Open Letter to the Labour Party 2d. 1944. A Five-Year Post-War Plan.......2d. Common Wealth in 1944 2d. *Agriculture 2d. *The Small Owner 2d. *Health 2d. *What Socialism Means to You 2d. *Socialism and the Bogies 2d. *Britain and the Peace 2d. * These Bulletins, Pamphlets and Leaflets are in production and are not yet available. COMMON WEALTH REVIEW. Published Monthly. Subscription 7s. per annum. Per Copy 6d. Published by C.W. PUBLISHING LTD., 4, Gower Street, London, W.C.1, and printed by Co-operative Printing Society Ltd., Rutherford Street, Newcastle-upon-Tyne. 15X/2/98/13